2017
DOI: 10.1103/physrevlett.119.055101
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of Macroscopic Flux Ropes at the Subsolar Magnetopause: Magnetospheric Multiscale Observations

Abstract: We report unambiguous in-situ observation of the coalescence of macroscopic flux ropes by the Magnetospheric Multiscale (MMS) mission. Two coalescing flux ropes with sizes of ~ 1 R E were identified at the subsolar magnetopause by the occurrence of an asymmetric quadrupolar signature in the normal component of the magnetic field measured by the MMS spacecraft. An electron diffusion region (EDR) with width of 4 local electron inertial lengths was embedded within the merging current sheet. The EDR was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 40 publications
(35 reference statements)
5
93
0
Order By: Relevance
“…Zhou et al () reported the presence of an ion jet reversal ( v iz, GSM = ± 200 km/s; Figure c) during a magnetopause crossing (17 November 2015—02:13:40–02:14:40 UT) corresponding to a “dissipative” interaction of two neighboring FTEs. Shortly after this crossing, at the peak of the southward ion velocity, a chain of small‐scale FTEs is observed, labeled as “FTE 1” and “FTE 2.” In particular, two FTEs centered at 02:20:48 UT and 02:21:24 UT are observed surrounded by two southward v iz peaks (02:17:30 UT and 02:22 UT) which met our selection criteria (Akhavan‐Tafti et al, ).…”
Section: Analysis and Resultsmentioning
confidence: 98%
“…Zhou et al () reported the presence of an ion jet reversal ( v iz, GSM = ± 200 km/s; Figure c) during a magnetopause crossing (17 November 2015—02:13:40–02:14:40 UT) corresponding to a “dissipative” interaction of two neighboring FTEs. Shortly after this crossing, at the peak of the southward ion velocity, a chain of small‐scale FTEs is observed, labeled as “FTE 1” and “FTE 2.” In particular, two FTEs centered at 02:20:48 UT and 02:21:24 UT are observed surrounded by two southward v iz peaks (02:17:30 UT and 02:22 UT) which met our selection criteria (Akhavan‐Tafti et al, ).…”
Section: Analysis and Resultsmentioning
confidence: 98%
“…The clear peaks of curl of E′ suggests that the electrons were not frozen-in to the magnetic field within this region (Goldman et al, 2016;Zhou et al, 2017). It has been reported that large guide field can magnetize electrons within the EDR (Eriksson et al, 2016;Zhou et al, 2017). It has been reported that large guide field can magnetize electrons within the EDR (Eriksson et al, 2016;Zhou et al, 2017).…”
Section: An Active X Line In the Exhaustmentioning
confidence: 92%
“…The thickness of this energy dissipation layer along N was 54 km/s * 0.33 s ≈ 18 km ≈ 12 d e . The clear peaks of curl of E′ suggests that the electrons were not frozen-in to the magnetic field within this region (Goldman et al, 2016;Zhou et al, 2017). The clear peaks of curl of E′ suggests that the electrons were not frozen-in to the magnetic field within this region (Goldman et al, 2016;Zhou et al, 2017).…”
Section: An Active X Line In the Exhaustmentioning
confidence: 96%
“…On the other hand, recent simulations and observations confirm that electron Kelvin‐Helmholtz instability can generate secondary MFR by forming electron vortex (Fermo et al, ; Huang, Lu, et al, ; Zhong et al, ). MFRs can coalesce to form larger MFRs, during which energy is dissipated and particles are energized (Wang et al, ; Zhou, Pang, et al, ; Zhou et al, ). Magnetic cloud in the solar wind, the prototype of which is MFR, may reconnect with the solar wind magnetic field around it and erode its magnetic flux (Ruffenach et al, ).…”
Section: Introductionmentioning
confidence: 99%